Tweeting Transit: An examination of social media strategies for transport information management during a large event - Cottrill, Caitlin; Gault, Paul; Yeboah, Godwin; Nelson, John D.; Anable, Jillian; Budd, Thomas (Elsevier, 2017)
Social media platforms are seeing increasing adoption by public transport agencies, as they provide a cost-effective, reliable, and timely mechanism for sharing information with passengers and other travellers. In this paper, we use a case study of the @GamesTravel2014 Twitter account to evaluate how this social media platform was used over the course of the 2014 Commonwealth Games in Glasgow, Scotland to provide and share transport-related information and respond to information requests. The case study provides an exemplar for the public co-ordination of information from multiple partners in a complex environment during a time of transport disruption. We evaluate both the structure and intent of the @GamesTravel2014 social media strategy via interviews with involved parties and an analysis of Tweets related to the account. Findings indicate the potential for future applications of social media by transport operators and authorities in producing a more effective network of communication with passengers.
Keywords: Social media; Public transport; Disruption; Co-operation